2013
DOI: 10.1186/1746-160x-9-7
|View full text |Cite
|
Sign up to set email alerts
|

In-office bacteria test for a microbial monitoring during the conventional and self-ligating orthodontic treatment

Abstract: This study investigated the microbial level of Streptococcus mutans and Lactobacillus spp. during an orthodontic treatment, and compare the data with untreated control subjects.Sixty young adult subjects were selected (average 20.5, DS 1.62), among which 40 underwent an orthodontic treatment (20 were treated with self-ligating brackets and 20 with conventional brackets) and 20 were controls. Plaque Index, salivary flow and buffering capacity of saliva were assessed before the beginning of the orthodontic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 12 publications
(9 reference statements)
4
72
2
Order By: Relevance
“…This result is in contrast with results of Pellegrini et al 19 and Mummola et al, 23 who found lower levels of bacteria with the SLB than with elastomeric ligating brackets. In conflict with this, van Gastel et al 21 found higher bacterial colonization with SLB.…”
Section: Microbiologic Evaluationcontrasting
confidence: 57%
See 1 more Smart Citation
“…This result is in contrast with results of Pellegrini et al 19 and Mummola et al, 23 who found lower levels of bacteria with the SLB than with elastomeric ligating brackets. In conflict with this, van Gastel et al 21 found higher bacterial colonization with SLB.…”
Section: Microbiologic Evaluationcontrasting
confidence: 57%
“…[18][19][20][21][22][23] Some researchers have reported that elastomeric ligated CB cause more plaque accumulation and periodontal inflammation than SLB, 6,18,19 whereas others reported no significant difference. 20 On the contrary, higher bacterial colonization and poorer periodontal health with SLB was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Pellegrini et al 24 demonstrated higher total bacteria and oral S mutans colonization in the CBs group at both 1 and 5 weeks after bonding. Similarly, in a recent study, Mummola et al 33 stated that the CBs showed statistically significantly higher lactobacilli colonization when compared to that of subjects treated with SLBs. However, Pithon et al 34 reported greater bacterial accretion on the SLBs than on the CBs ligated with elastic ligature.…”
Section: Amount Of Microbial Colonizationmentioning
confidence: 99%
“…11,[14][15][16][17][18]23,24,[32][33][34] Only some studies compare SLBs with CBs for microbial colonization after bonding. [32][33][34] Nonetheless, these studies have showed conflicting results. Thus, this topic remains controversial.…”
Section: Amount Of Microbial Colonizationmentioning
confidence: 99%
“…In the absence of such treatment, maxillary canine impaction requires comprehensive orthodontic-surgical treatment, including surgical exposure of the canine crown and orthodontic traction to bring the impacted canine into occlusion (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%